Uso de matrices alodérmicas en cirugía plástica periodontal: reporte de un caso - Ardila-M., Carlos Martín (Revista Facultad de Odontología Universidad de Antioquia, 2009)
Treatment of gingival recession has been a common practice in periodontics. Patients often present with multiple areas requiring treatment but palatal anatomy may limit the amount of autogenous tissue that can be harvested, limiting the number of procedures that can be performed. There are patients who may not desire to have additional tissue transplanted from the palate, due to increased pain and morbidity associated with multiple transplant procedures. This article presents a case report of multiple recessions. The patient presented with a shallow palate and he declined to have both side of his palate surgically harvested. As an alternative, an acelular dermal matrix allograft was utilized to correct these mucogingival defects avoiding the requirement for a second palatal surgical procedure.